The new realities : - Drucker, Peter F. (HarperBusiness, 1994)
This is an ambitious book that casts its net over a wide range of subjects. Written in the United States by an American, it does not confine itself to American topics, it deals fully as much with government, society, and economy in japan, in Western Europe, in Russia, and in the third World of developing countries.